The Justice of Earnings in Dual-Earner Households - Stefan Liebig; Carsten Sauer; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The rise in female labor market participation and the growth of "atypical" employment arrangements has, over the last few decades, brought about a steadily decreasingpercentage of households in which the man is the sole breadwinner, and a rising percentage of dual-earner households. Against this backdrop, the present paper investigates the impact of household contexts in which the traditional male breadwinner model has been called into question on individuals' subjective evaluations of the equity or inequity of their personal earnings. In the first step, based on social production function theory, we derive three criteria used by individuals to evaluate the fairness or justice of their personal earnings: compensation for services rendered, coverage of basic needs, and the opportunity to earn social approval. In the second step, we apply considerations from household economics and new approaches from gender research to explain why men's and women's evaluations of justice are determined to a considerable degree by the specific situation within their household - for example, by the status and income relation between the two partners. The assumptions derived regarding gender-specific patterns in justice attitudes are then tested on data from the German Socio-Economic Panel Study (SOEP) from the year 2007. We find that, among women, the perceived justice of personal earnings depends much more strongly on the particular household context. At the same time, opportunities for social comparison within the household and the relation between the woman's personal income and that of her husband play central roles. Men's justice evaluations, in contrast, are determined to a much greater extent by whether their income allows them to conform to traditional gender norms and concepts of "masculinity", and by so doing, to gain social approval outside the household as well.
Keywords: 330